Design of Random Warranty and Maintenance Policy: From a Perspective of the Life Cycle - Lijun Shang; Xiguang Yu; Liying Wang; Yongjun Du (Mathematics, 2022)
Driven by digital technologies, it is possible that high-tech equipment management personnel use monitored job cycles to ensure products’ operation and maintenance over their life cycle. By means of monitored job cycles, this paper designs two categories of random maintenance policies: a two-stage two-dimensional free repair warranty (2DFRW) policy and a random hybrid periodic replacement (RHPR) policy. The 2DFRW policy is performed to ensure the product’s operation and maintenance over the warranty stage. Under such a policy, a product is minimally repaired at each failure, and regions of the second-stage warranty are set to be diverse to remove all inequities produced by limitations of the first-stage warranty. The warranty cost of two-stage 2DFRW is built and discussed. The RHPR policy is modeled to ensure the product’s operation and maintenance over the post-warranty stage. Under this policy, depending on the final expiry of the two-stage 2DFRW, a bivariate random periodic replacement (BRPR) policy and a univariate random periodic replacement (URPR) policy are skillfully used to reduce the maintenance cost over the post-warranty stage and maximally extend the residual useful time of the product through the warranty. The expected cost rate over the product’s operation and maintenance cycle is derived on the basis of renewal rewarded theorem. The optimal RHPR policy is analyzed by minimizing the cost rate. The presented models are numerically analyzed to explore hidden characteristics.